ð˜—ð˜¦ð˜ð˜µð˜¢ð˜®ð˜ªð˜¨ð˜³ð˜¢ð˜µð˜¶ð˜´ ð˜ªð˜£ð˜ªð˜£ð˜°ð˜¤ð˜¢ N. SP. FROM BRAZIL (Nemata, Haplolaimidae) - Monteiro, Ailton Rocha; Choudhury, M. Menhazuddin (REVISTA DE AGRICULTURA, 2020)
ð˜—ð˜¦ð˜ð˜µð˜¢ð˜®ð˜ªð˜¨ð˜³ð˜¢ð˜µð˜¶ð˜´ ð˜ªð˜£ð˜ªð˜£ð˜°ð˜¤ð˜¢ N. SP. FROM BRAZIL (Nemata, Haplolaimidae)